Tether response of offshore Triceratops under hurricane conditions. (May 2023) - Chandrasekaran, Srinivasan; Shah, Bharat; Chauhan, Yogesh J.
Abstract: The form-dominant approach is increasingly adopted in offshore platform design; triceratops is one of the very recent examples. These platforms are position-restrained by taut-moored tethers, which govern the dynamic response under extreme environmental loads. Due to the partial isolation of the deck from the buoyant legs in the presence of ball joints, sub-structure analysis is more critical. The present study examines the tether response of triceratops in 2400 m water-depth under hurricane conditions caused by 10-yr, 100-yr, and 1000-yr Gulf of Mexico (GoM) storms. The numerical studies show that the Peak-Wave case governs the dynamic tension variation of tethers for the chosen hurricane conditions. For the 100-yr and 1000-yr storms, they are about 15% and 45% higher than 10-yr storms, respectively. However, the maximum axial tensile stresses are about 8% of the yield, ensuring a no-rupture condition of the tethers. The service lives of the tethers for 10-yr storms are about one-third that of 100-yr and 1000-yr storms. A positive minimum tension for all load cases confirms no slackening of the tethers.